2007
DOI: 10.1101/gr.6249707
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary rate analyses of orthologs and paralogs from 12 Drosophila genomes

Abstract: The newly sequenced genome sequences of 11 Drosophila species provide the first opportunity to investigate variations in evolutionary rates across a clade of closely related species. Protein-coding genes were predicted using established Drosophila melanogaster genes as templates, with recovery rates ranging from 81%-97% depending on species divergence and on genome assembly quality. Orthology and paralogy assignments were shown to be self-consistent among the different Drosophila species and to be consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
117
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(132 citation statements)
references
References 48 publications
(48 reference statements)
14
117
1
Order By: Relevance
“…Protein-coding and non-protein-coding genes were computed using a modified version of the Ensembl pipeline (Supplementary Notes 14). Gene orthology assignment followed a procedure implemented previously 69 . Orthology rate estimation was performed with PAML 70 using the model of ref.…”
Section: Methods Summarymentioning
confidence: 99%
“…Protein-coding and non-protein-coding genes were computed using a modified version of the Ensembl pipeline (Supplementary Notes 14). Gene orthology assignment followed a procedure implemented previously 69 . Orthology rate estimation was performed with PAML 70 using the model of ref.…”
Section: Methods Summarymentioning
confidence: 99%
“…We note that the TEs that are diverged from the dominant sequences in the piRNA pool are expected to enjoy less suppression and thus more replicative transposition. Also, several studies of the molecular evolution of genes in the piRNA pathway have reported evidence for adaptive evolution (Heger & Ponting 2007;Obbard et al 2009). The divergencebased escape to these two sequence-similarity-based mechanisms (piRNA pathway and ectopic exchange) has the potential to drive an additional TE-host coevolutionary arms race directly at the TE sequences.…”
Section: Piwi-interacting Rna As a Competing Model For Containmentmentioning
confidence: 99%
“…We used maximum-likelihood methods (Yang 2007) genes among other D. melanogaster annotated genes (see Table 2 for d N /d S ratio and (Heger and Ponting 2007;Kolaczkowski et al 2011), the branch leading to D. melanogaster was not significant (Kolaczkowski et al 2011). The differences between studies are not surprising given the fundamental differences in methodology (comparing relative rates of amino acid substitutions of entire coding sequences among all genes vs. identification of a subset of sites or branches that recurrently substituted across the phylogeny).…”
Section: Candidate Genesmentioning
confidence: 99%